(untitled) (Perioperaciina Medicina, 2021)
Infectious complications in surgery occupy a significant place among the causes of death and increase in the cost of medical care for various pathologies. Antibiotic prophylaxis takes one of the first places in the perioperative period, in addition to surgical treatment and compliance with the rules of asepsis and antiseptics. Laxers is a new drug in the cephalosporin group, consisting of a combination of cefoperazone and sulbactam. It has a wide range of action on gram(-) and anaerobic flora and antistaphylococcal activity, which is not inferior to cefoperazone. Due to sulbactam, it has antimicrobial activity against Pseudomonas aeruginosa and Acinetobacter spp. This article describes the main properties and advantages of Laxers over other cephalosporins in this group as the drug of choice in the treatment of surgical pathologies and alternative antibiotic prophylaxis in the perioperative period in severe patients at risk of contamination of the operating field with hospital flora.